Warfarin-Induced Supratherapeutic Anticoagulation Presenting as an Iliopsoas/Iliacus Haematoma with Lower Gastrointestinal Haemorrhage - Mishra, Subhasis; Hegde, Raghavendra Shivaram (Indian Journal of Pharmacy Practice, 2026)
Warfarin remains one of the most frequent causes of serious bleeding-related hospital admissions because of its narrow therapeutic index and unpredictable inter-individual response, and the iliopsoas/iliacus compartment is an under-recognised site of anticoagulant-related haemorrhage that can be mistaken radiologically for an abscess. A 44-year-old man with an eleven-year history of warfarin therapy for deep vein thrombosis presented with a fifteen-day history of bleeding per rectum together with one day of abdominal pain and vomiting. He was severely anaemic (Haemoglobin 4.2 g/dL) with a critically elevated international normalised ratio of 9.23. Ultrasonography and computed tomography demonstrated a rapidly enlarging collection in the left iliacus muscle that was radiologically favoured as an abscess, but the absence of fever together with the coagulation profile pointed instead to an expanding haematoma. Critically, pharmacy dispensing records confirmed that the patient had been concurrently self-administering warfarin alongside a newly prescribed rivaroxaban regimen-a medication-reconciliation failure that was the proximate cause of the supratherapeutic anticoagulant state. Management included withholding warfarin, intravenous Vitamin K, multiple packed red cell transfusions, empirical antibiotic cover, and ultrasound-guided drainage, with gradual clinical improvement. Intravenous Vitamin K was selected as the reversal agent in preference to fresh frozen plasma or four-factor prothrombin complex concentrate, which was appropriate given the patient's haemodynamic stability and the absence of a requirement for emergency surgical intervention. Causality was assessed using the Naranjo Adverse Drug Reaction Probability Scale-with the INR applied as a validated pharmacodynamic surrogate for toxic warfarin exposure-yielding a score of 8 and classifying the event as a probable adverse drug reaction. Iliopsoas/iliacus haematoma is a potentially life-threatening complication of supratherapeutic warfarin therapy that can closely mimic an abscess on imaging. Clinicians and pharmacists must correlate any newly detected intra-abdominal collection with the coagulation profile before assuming an infective cause, and must ensure structured anticoagulant reconciliation at every point of transition between anticoagulant classes.
Keywords: Adverse Drug Reaction; Anticoagulant-Associated Haemorrhage; Iliopsoas; Haematoma; Naranjo Scale; Supratherapeutic INR; Warfarin